Towards a Spirituality À Rebours?: Traces of Post-Secular Discourse in Selected Movies of Małgorzata Szumowska - Mazur, Daria (Studia religiologica, 2018)
The paper aims at a scrutiny of traces showing that Małgorzata Szumowska, in several of her mov-ies (33 sceny z życia [33 Scenes from Life]; Body/Ciało [Body]; W imię... [In the Name of]; Twarz[Mug]), plays with the models of metaphysical cinema, at the same time juxtaposing them with phe-nomena and processes connected with the shaping of the so-called “new spirituality.” Szumowska creates her movies along the lines of the thinking of postmodern philosophers who build on the differences between religiosity and spirituality. Films that at first glance seem secular and avoid straightforward questions about faith (questions that would be strictly theological), make manifest the traits of human existence in the postmodern world, an existence marked with insatiability, lone-liness, despair, disorientation, doubt, and emptiness, and attempt to find a cinematic language that would visualize the reality and the phenomenon of the struggle between what is carnal and what is spiritual.